2018
DOI: 10.1002/pip.3017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of front contact layers on performance of Cu(In,Ga)Se2 solar cells in relaxed and metastable states

Abstract: We studied the impacts of front contact layers composed of transparent conducting oxide (TCO) and transparent oxide semiconductor (TOS) layers on the performance of Cu(In,Ga)Se 2 (CIGS) solar cells with glass/Mo/CIGS/CdS/TOS/TCO in relaxed and metastable states. After annealing under illumination, the CIGS solar cells with KF and NaF postdeposition treatments exhibited metastable increases in open-circuit voltage, fill factor, and the resulting conversion efficiency with a metastable decrease in short-circuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…W190113). HLS treatment increased the V OC and carrier concentration ( N CV ) and reduced J SC, whereas the HS treatment yielded opposite results similar to the previous reports on alkali‐treated samples . The change in the width of the space charge region (SCR) was consistent to the change in N CV .…”
supporting
confidence: 84%
See 4 more Smart Citations
“…W190113). HLS treatment increased the V OC and carrier concentration ( N CV ) and reduced J SC, whereas the HS treatment yielded opposite results similar to the previous reports on alkali‐treated samples . The change in the width of the space charge region (SCR) was consistent to the change in N CV .…”
supporting
confidence: 84%
“…Such improvement has a turn-on time constant in the order of a few minutes and turn-off time constant in the order of a day or months. [29] A metastable phenomenon on non alkali-treated CIGS solar cells due to a Zncompound buffer layer and CIGS thin films under light illumination and bias has been observed in earlier studies. [30,31] Previous studies revealed that HLS improved the fill factor (FF) and η due to a rearrangement of the S/(S þ O) atomic ratio in the CBD-ZnS(O,OH) buffer layer to adjust the conduction band offset at the ZnS(O,OH)/CIGS interface.…”
mentioning
confidence: 65%
See 3 more Smart Citations